PENGARUH PENGENDALIAN INTERN DAN TINDAK LANJUT TEMUAN AUDIT TERHADAP KUALITAS LAPORAN KEUANGAN YANG BERIMPLIKASI TERHADAP PENCEGAHAN FRAUD - Kustiawan, Memen (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2016)
The Influence of Internal Control and Audit Findings Follow-up Toward the Quality of Financial Statement Which Imply in Preventing Fraud. This research aimed to find out the influence of internal control and audit findings follow-up toward the quality of financial statement which imply in preventing fraud. The analysis sample of this research was all Government Universities (Perguruan Tinggi Negeri) in West Java which was 15 of those universities were the population of this research (census). Besides giving questionnaires and having interview, doing observation and studying documentation of divisions that handle the financial report in each university were necessary to get the secondary data and interview result of Internal Auditor, if the university was part of Internal Auditor. According to the output of counting path analysis by using Lisrel 8.3 program, it was concluded that the internal control (20.27%) was more dominant than the audit findings follow-up (12.27%) in influencing the quality of financial statement and the influence of financial statement quality in preventing fraud was 2.89%. Based on the whole internal control variables, audit findings follow-up, and quality of financial statement altogether showed the influence toward the fraud prevention was 35.96%.